Are early writers and readers more successful than their counterparts? - López-Agudo, Luis Alejandro; Marcenaro-Gutiérrez, Óscar David (My University, 2016)
There exists an increasing number of scientific contributions focused on the influence of the attendance to early childhood and/or preprimary education on the future academic track of the students, which employ the quarter of birth of the student as a proxy for infants’ maturity. The present work goes a step further by employing information on the precise time when children begin to exhibit the basic competences (reading and writing), controlling by the effect of the quarter of birth, for andalusian students aged 10-11 and 14-15. This study uses descriptive analysis as starting point to specify multivariate estimates for the age at which the student began to read and write, together with students’ quarter of birth. Moreover, the effect of these variables on the likelihood of repeating a course has also been analyzed. Results show that the quarter of birth and the age when the student began to read and write affect students’ early academic achievement –primary education– and the likelihood of repeating, but this effect is weakened once non-repeaters reach age 14-15. In addition, students from households where parents have a low level of education present a late start in beginning to read and write and, thus, lower achievement than their older counterparts. This highlights the need to increase the investments in public early education for students living in this kind of families –by increasing the supply of public early education places and scholarships–, so they can develop these competences as soon as possible. This kind of interventions could have a relevant role in fostering higher social mobility.
Keywords: Rendimiento académico; Maturity; Writing; Reading; Primary education; Grade repetition